Relationship of renewable energy consumption to economic, environmental and institutional factors in Europe. (November 2021) - Filimonova, I.V.; Nemov, V.Y.; Komarova, A.V.; Mishenin, M.V.; Kozhevin, V.D.
Abstract: Challenges caused by global climate change arise several environmental, social, and energy production issues. These problems firstly concern interest of resource extraction countries, triggering inter-fuel competition in both directions supply and consumption of energy resources. Moreover, significantly increased green agenda leads countries to foster shifting to green energy production and discovering factors of most influential on the acceleration of RES consumption. The paper focuses on the impact assessment of economic, environmental and institutional factors of the country development on the future consumption of renewable energy sources (RES). To achieve the purpose of the study a panel data analysis method was used. The analysis was conducted for 41 European countries for 1995–2018, with countries being divided into members of Organization for Economic Co-Operation and Development (OECD)/non-OECD and Extractive/non-Extractive. Four hypotheses were tested under the research: (1) Developing countries are characterized by the negative impact of CO2 emissions on RES consumption, while developed countries — the opposite; (2) Non-RES consumption reflects inter-fuel competition, expressed in a negative relationship with the RES; (3) Prices increase for non-RES contributes to growth of RES consumption; (4) Institutional factors reflect the level of "market freedom and mobility" of the country and contribute to the development of RES. The authors confirmed all hypothesizes and showed that economic, particularly GDP, and institutional factors had the greatest impact on all countries' RES consumption, while the environmental aspect is weakly significant for non-extractive countries. Consumption of fossil resources had a negative impact and confirmed the presence of inter-fuel competition.